Vaccine uptake and barriers to vaccination among at-risk adult populations in the US - Irina Kolobova; Mawuli Kwame Nyaku; Anna Karakusevic; Daisy Bridge; Iain Fotheringham; Megan O'Brien (Taylor & Francis Group, 2022)
To reduce morbidity and mortality associated with vaccine-preventable diseases (VPD), it is imperative that vaccination programs are implemented and prioritized throughout all stages of life across all populations. This study aimed to determine vaccine uptake and barriers to vaccination against VPDs among at-risk adult populations in the United States. We conducted a systematic literature review for articles published between January 2010 and June 2020 and identified 153 publications. The review identified 17 at-risk populations. Vaccine uptake was suboptimal among many populations, with factors including age, gender, and disease severity, associated with uptake. This review identified several barriers that impact vaccine uptake among at-risk populations, with concerns over safety, vaccine costs, lack of insurance, and lack of provider recommendation commonly reported across populations. Embracing a national life-course immunization framework that integrates developing policies, guidelines, and education would be a step to addressing these barriers.